Public knowledge, attitude, and acceptance toward COVID-19 vaccines in Palestine: a cross-sectional study - Mohammed Al-kafarna; Sajeda Ghassan Matar; Hossam Waleed Almadhoon; Bashar Khaled Almaghary; Mohamed Sayed Zaazouee; Asmaa Ahmed Elrashedy; Dalia Sami Wafi; Sami D. Jabari; Omar H. Salloum; Eman Ahmed Ibrahim; Hala ZI Alagha; Elfatih A. Hasabo; et al. (BMC, 2022)
Abstract Background The consequences of the COVID-19 pandemic on physical and mental health in addition to the global economy are huge. Vaccination is a pivotal measure to decrease COVID-19 morbidity and mortality and to help bring the pandemic under control. Yet, success of the vaccination process depends on the population's willingness to be vaccinated which may be determined by their level of knowledge about and trust in currently available COVID-19 vaccines. Therefore, this study aims to assess the knowledge, attitude, and acceptance of Palestinians towards COVID-19 vaccines. Methods A national cross-sectional study was distributed in different Palestinian regions to assess the knowledge and attitude of Palestinians toward COVID-19 vaccines using an online questionnaire, it included three sections; sociodemographic characteristics, knowledge assessment questions, and attitude assessment questions. Results A total of 6226 participants completed the questionnaire; among them, 41.36% believed that vaccines are safe, 69.02% agreed that vaccines are vital to protect from COVID-19; in addition, 55.1% approve administering the vaccine once available, and 37.86% do not believe their benefits outweigh the risks. The Source of information for 22.07% of participants in social media, while 11.92% rely on health care providers. Participants' attitudes and knowledge were significantly affected by gender, governorate, age, education level, and marital status (P <0.001). Conclusion The findings suggest that there is good knowledge and attitude toward the vaccination process against COVID-19 in Palestine, although low acceptance was detected. Awareness campaigns are required to spread reliable knowledge about COVID-19 vaccines.